Działalność doktora Henryka Jordana na rzecz dzieci i młodzieży. W poszukiwaniu współczesnych odniesień - Rutkowski, Jarosław; Semrau, Katarzyna (Biuletyn Historii Wychowania, 2023)
The activity of Dr. Henryk Jordan played an important role in the development of health education in Galicia, Eastern Europe, in the late 19th and the early 20th centuries. This article revolves around Jordan’s concept of the development of the physical condition of Poles and the physical education system for children and adolescents. Henryk Jordan’s actions have been re-interpreted in the context of building various educational establishments. His efforts, focused on organizing free time for students, were aimed at ensuring their sustainable development. In this respect, the creation of the City Park was Henryk Jordan’s great achievements, serving the physical education of children and adolescents and promotion of mass sport. This organization of public space can be a valuable guideline for architects and educators who create friendly spaces for children and young people. At the same time, the article pinpoints that the target audience and the users are members of local communities whose voices should always be heard and considered. When this happens, they form a relationship with friendly space which takes them into an existential dimension.